VD_FINDINFO AM 53/09 - 45/2009 vom 9. Oktober 2009 - VD Tribunal cantonal (2009)
RETARD, DÉCISION D'IRRECEVABILITÉ | 1 al. 1 LAMal, 38 al. 1 LPGA, 39 LPGA, 56 al. 1 LPGA, 58 LPGA, 60 al. 1 LPGA, 60 LPGA, 19 al. 1 LPA-VD, 2 LPA-VD, 20 al. 1 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. c LPA-VD, 95 LPA-VD